A single-atom modified MoSe2 piezoelectric catalyst, its preparation method and application

CN122937826APending Publication Date: 2026-10-20NANJING NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611393185.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,现有MoSe2仍存在活性位点不足与载流子复合严重等问题,限制了在污染物高效降解及废水资源化转化领域中的应用

Benefits of technology

[0027]本发明所述催化剂利用压电效应将机械能转化为化学能,并通过单原子改性技术解决了压电催化剂本身的活性位点不足、载流子易复合的问题。通过在同一反应体系中,实现氧化降解与还原产气两个半反应的高效协同,避免了压电电子的浪费,最终实现了水体中废弃有机碳氢资源向高附加值合成气体的回收与利用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a metal single-atom modified MoSe2 piezoelectric catalyst, its preparation method, and its application. The catalyst uses MoSe2 as a substrate, with Co single atoms loaded onto the MoSe2 surface through a reduction reaction. Loading Co single atoms onto the MoSe2 surface not only increases the number of catalytically active sites but also allows the Co single atoms to act as electron-trapping sites, effectively capturing electrons generated by piezoelectric polarization, promoting carrier separation, and suppressing the rapid recombination of electron-hole pairs, thus improving the problem of fast carrier recombination rates in existing piezoelectric catalysts. When this catalyst is used in a piezoelectric catalytic coupling persulfate system, it can not only efficiently activate persulfate to achieve efficient degradation of recalcitrant organic pollutants such as sulfamethoxazole, but also utilize the electrons generated during the piezoelectric catalysis process to promote water reduction to produce hydrogen and the reduction of carbon-containing intermediates to CO, realizing the conversion of organic carbon resources in wastewater into syngas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of piezoelectric catalyst technology, and specifically relates to a metal single-atom modified MoSe2 piezoelectric catalyst, its preparation method and application. Background Technology

[0002] In recent years, with the rapid development of industrialization and urbanization, the accumulation of recalcitrant organic pollutants in wastewater has posed a serious threat to ecological security and human health. Among these, sulfonamide antibiotics such as sulfamethoxazole (SMX), due to their widespread use in medicine and animal husbandry, can continuously enter the aquatic environment through medical wastewater and aquaculture wastewater. These pollutants are characterized by their stable structure and poor biodegradability, easily disrupting the balance of aquatic ecosystems.

[0003] Organic pollutants in wastewater are not only sources of pollution but also rich in usable organic carbon resources. Converting these organic carbon components into high-value-added energy substances provides a new approach to achieving synergistic pollution control and resource recovery. Syngas, composed of H2 and CO, serves as an important chemical raw material and energy carrier, possessing significant application value. Compared to traditional wastewater treatment methods that completely mineralize organic pollutants, further converting the carbon resources in pollutants into syngas can improve resource utilization efficiency in wastewater treatment. However, existing wastewater treatment technologies focus solely on pollutant removal, with limited research on the high-value utilization of organic hydrocarbon resources in wastewater. Therefore, developing a wastewater resource recovery technology capable of simultaneously removing recalcitrant organic pollutants and producing syngas is crucial for promoting the coordinated development of environmental governance and energy utilization.

[0004] Persulfate (PDS) is widely used in the treatment of recalcitrant organic pollutants due to the strong oxidizing power, long half-life, and wide applicable pH range of the sulfate radicals generated during activation. However, traditional PDS activation methods require significant energy or material consumption and involve harsh reaction conditions. In contrast, piezoelectric catalysis technology shows great application potential. This technology can directly convert widely available mechanical energy in the environment (such as wind energy, tides, and water flow) into chemical energy through the piezoelectric effect, without the need for an external power source. It can induce piezoelectric catalysts to generate piezoelectric charges that directly break the peroxy (OO) bonds in PDS, generating reactive oxygen species. This provides a promising new strategy for achieving green, environmentally friendly, and low-consumption persulfate activation.

[0005] Among numerous piezoelectric catalysts, layered transition metal chalcogenides (MoSe2) are considered ideal due to their excellent piezoelectric response characteristics, good mechanical flexibility, large specific surface area, and sensitivity to minute mechanical stresses. However, existing MoSe2 catalysts still suffer from problems such as insufficient active sites and severe carrier recombination, limiting their application in the fields of efficient pollutant degradation and wastewater resource conversion. Summary of the Invention

[0006] Objectives of the Invention: The first objective of this invention is to provide a single-atom modified MoSe2 piezoelectric catalyst with abundant active sites and high carrier separation efficiency; the second objective of this invention is to provide a method for preparing the single-atom modified MoSe2 piezoelectric catalyst; and the third objective of this invention is to provide applications of the single-atom modified MoSe2 piezoelectric catalyst.

[0007] Technical solution: The metal single-atom modified MoSe2 piezoelectric catalyst of the present invention uses MoSe2 as a substrate and Co single atoms are loaded on the surface of MoSe2 through a reduction reaction.

[0008] Preferably, the loading of Co single atoms in the catalyst is 0.059~1.05 wt%. Different Co loadings affect the syngas yield, which exhibits a volcanic distribution with increasing Co content, first rising and then falling. When the Co single-atom loading is too low, there are insufficient catalytic active sites; when the loading is too high, excessive Co is prone to aggregation, which not only masks some active sites on the MoSe2 surface but also limits the carrier separation efficiency, thereby reducing catalytic performance.

[0009] Preferably, the catalyst exhibits a nanoflower-like structure composed of ultrathin nanosheets assembled as a whole.

[0010] The preparation method of the metal single-atom modified MoSe2 piezoelectric catalyst of the present invention includes the following steps:

[0011] (1) Preparation of MoSe2 powder;

[0012] (2) MoSe2 powder was uniformly dispersed in a solvent, and a cobalt salt solution was added under stirring. After stirring evenly, a reducing agent was added to carry out a reduction reaction. After the reaction was completed, the solid was collected, washed, and dried to obtain a Co single-atom modified MoSe2 piezoelectric catalyst.

[0013] Preferably, in step (1), the method for preparing MoSe2 powder is as follows: NaBH4, Se powder and Na2MoO4·2H2O are dissolved in water, mixed evenly and then subjected to a hydrothermal reaction; after the reaction is completed, the mixture is cooled, the precipitate is collected, washed and dried to obtain black MoSe2 powder; wherein, the molar ratio of NaBH4, Se powder and Na2MoO4·2H2O is 3~4:1.9~2:1.

[0014] Preferably, in step (1), the hydrothermal reaction temperature is 180~210℃ and the reaction time is 18~20 h.

[0015] Preferably, in step (2), the reducing agent is NaBH4, and the molar ratio of cobalt ions in MoSe2 and cobalt salt to NaBH4 is 393:1~18:40.

[0016] Preferably, in step (2), the reduction reaction is carried out at 20~30℃ for 12~16 h.

[0017] Preferably, in step (2), the solvent is water.

[0018] Preferably, the washing process involves washing three times each with deionized water and anhydrous ethanol.

[0019] Preferably, the drying process is carried out under vacuum, with a drying temperature of 50-60 °C and a drying time of 12-16 h.

[0020] The present invention relates to the application of the metal single-atom modified MoSe2 piezoelectric catalyst in the piezoelectric catalytic coupling of persulfate degradation of organic pollutants in wastewater to simultaneously generate H2 and CO syngas.

[0021] Preferably, the persulfate is perdisulfate.

[0022] Preferably, the organic pollutant is a sulfonamide antibiotic.

[0023] Preferably, the sulfonamide antibiotic is sulfamethoxazole.

[0024] The application method is as follows: The Co-modified piezoelectric catalyst is uniformly dispersed in an aqueous solution containing organic pollutants, transferred to a gas-tight reactor, and subjected to complete vacuum degassing. High-purity argon is repeatedly introduced to remove residual air from the system, and the reactor is pressurized to 1-5 bar argon pressure. Before ultrasonic activation, PDS solution is injected into the gas-tight reactor, and then the ultrasonic-driven reaction begins. During this process, the degradation of recalcitrant organic pollutants and the simultaneous generation of high-value-added syngas H2 and CO are simultaneously achieved within the system.

[0025] Invention Mechanism: This invention uses MoSe2 loaded with Co single atoms as a piezoelectric catalyst. Under the action of ultrasonic mechanical energy, the piezoelectric catalyst deforms to generate a piezoelectric polarization field, which in turn generates electron-hole pairs. The Co single atoms anchored on the surface of MoSe2 can efficiently capture electrons, significantly suppress the recombination of electrons and holes, and improve the carrier separation efficiency.

[0026] Under ultrasound, the electron-rich Co single-atom sites act as active sites for activating PDS, efficiently transferring electrons to PDS, breaking its O2O bonds, and activating it to generate highly oxidizing reactive oxygen species. These induced reactive oxygen species, in conjunction with piezoelectric holes, oxidize organic pollutants into inorganic carbon sources such as carbonates. Subsequently, piezoelectric electrons further reduce the aforementioned carbonate intermediates to CO; simultaneously, another portion of piezoelectric electrons reduces H2O to H2, ultimately yielding high-value-added syngas composed of H2 and CO.

[0027] The catalyst described in this invention utilizes the piezoelectric effect to convert mechanical energy into chemical energy, and solves the problems of insufficient active sites and easy recombination of charge carriers in piezoelectric catalysts through single-atom modification technology. By achieving efficient synergy between the two half-reactions of oxidation degradation and reduction gas production in the same reaction system, the waste of piezoelectric electrons is avoided, ultimately realizing the recovery and utilization of waste organic hydrocarbon resources in water bodies into high-value-added syngas.

[0028] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The present invention loads Co single atoms on the surface of MoSe2, which not only increases the catalytic active sites, but also the Co single atoms can be used as electron trapping sites to effectively trap electrons generated by piezoelectric polarization, promote carrier separation, inhibit the rapid recombination of electron-hole pairs, and improve the problem of fast carrier recombination rate of existing piezoelectric catalysts; (2) The catalyst of the present invention is prepared by hydrothermal method combined with wet chemical impregnation reduction method. The raw materials required are simple, readily available and inexpensive. The preparation process is simple, the reaction conditions are mild and environmentally friendly, which is conducive to its application in the field of actual wastewater treatment and resource utilization; (3) The Co / MoSe2 piezoelectric catalytic coupling persulfate reaction system constructed in the present invention has excellent pollutant degradation and resource conversion performance under ultrasonic driving, of which the SMX degradation rate reaches 99.8% and the syngas production reaches 465.6 μmol g. -1 The H2 production was 367.1 μmol g. -1 CO production was 98.5 μmolg. -1The syngas production is 2.8 times that of unmodified MoSe2; (4) The piezoelectric catalytic coupling persulfate reaction system constructed in this invention has both pollutant removal and resource utilization functions. In the same reaction system, the organic pollutants in the wastewater are first oxidized into inorganic carbon intermediates such as carbonates, and then reduced to CO under the action of piezoelectric electrons, and hydrogen is produced by water reduction, thereby achieving efficient removal of organic pollutants and conversion of organic hydrocarbon resources in wastewater into syngas. Attached Figure Description

[0029] Figure 1 These are the XRD patterns of the catalysts prepared in Examples 1-5 and Comparative Example 1;

[0030] Figure 2 These are Raman diagrams of the catalysts prepared in Example 2 and Comparative Example 1;

[0031] Figure 3 This is a TEM image of the catalyst prepared in Comparative Example 1;

[0032] Figure 4 This is a TEM image of the catalyst prepared in Example 2;

[0033] Figure 5 This is the EDS energy spectrum of the catalyst prepared in Example 2;

[0034] Figure 6 The graph shows the syngas production of the catalysts prepared in Examples 1-5 and Comparative Example 1 under the condition of 50 mL, 10 mg / L SMX solution.

[0035] Figure 7 The graph shows the SMX degradation rate of the catalysts in Examples 1-5 and Comparative Example 1 under the condition of 50 mL, 10 mg / L SMX solution.

[0036] Figure 8 This is a graph showing the syngas yield and SMX degradation rate of the catalyst under different concentrations of SMX solution in Example 2;

[0037] Figure 9 This is a graph showing the cyclic stability of the catalyst in Example 2 under conditions of 50 mL, 10 mg / L SMX solution. Detailed Implementation

[0038] The technical solution of the present invention will be further described below with reference to the embodiments.

[0039] Example 1

[0040] The metal single-atom modified MoSe2 piezoelectric catalyst of the present invention is prepared by the following steps:

[0041] (1) Preparation of MoSe2 powder

[0042] 0.608 g sodium borohydride, 0.632 g selenium powder, and 0.968 g sodium molybdate dihydrate were added to 150 mL of deionized water and stirred for 30 min to ensure thorough mixing. The resulting mixture was then transferred to a 100 mL polytetrafluoroethylene-lined stainless steel high-pressure reactor and subjected to hydrothermal reaction at 210 °C for 20 h. After the reaction, the mixture was allowed to cool naturally to room temperature. The resulting product was washed three times sequentially by centrifugation with deionized water and anhydrous ethanol, and then further processed at 50 °C. o Black MoSe2 powder was obtained by drying under vacuum for 16 h.

[0043] (2) Preparation of 0.05Co / MoSe2 piezoelectric catalyst

[0044] 100 mg of the prepared MoSe2 powder was uniformly dispersed in 100 mL of deionized water and stirred to form a homogeneous dispersion. While continuously stirring, 0.05 mL of a 20 mM cobalt chloride hexahydrate solution was added dropwise to the dispersion. After stirring for 30 min, 2 mL of a 20 mM sodium borohydride solution was added dropwise, and the mixture was stirred continuously at room temperature (20–30 °C) for 14 h. After the reaction was complete, the resulting product was washed three times sequentially with deionized water and anhydrous ethanol by centrifugation, and then dried overnight under vacuum to obtain a Co-supported MoSe2 piezoelectric catalyst, named 0.05Co / MoSe2. The mass fraction of Co in the catalyst was 0.059%.

[0045] Example 2

[0046] Based on Example 1, the amount of cobalt chloride hexahydrate added was changed to 0.15 mL, while other conditions remained unchanged, to obtain a Co single-atom-supported MoSe2 piezoelectric catalyst, named 0.15Co / MoSe2, with a Co element mass fraction of 0.176%.

[0047] Example 3

[0048] Based on Example 1, the amount of cobalt chloride hexahydrate added was changed to 0.3 mL, while other conditions remained unchanged, to obtain a Co single-atom-supported MoSe2 piezoelectric catalyst, named 0.3Co / MoSe2, with a Co element mass fraction of 0.352%.

[0049] Example 4

[0050] Based on Example 1, the amount of cobalt chloride hexahydrate added was changed to 0.6 mL, while other conditions remained unchanged, to obtain a MoSe2 piezoelectric catalyst supported on Co single atoms, named 0.6Co / MoSe2, with a Co element mass fraction of 0.702%.

[0051] Example 5

[0052] Based on Example 1, the amount of cobalt chloride hexahydrate added was changed to 0.9 mL, while other conditions remained unchanged, to obtain a Co single-atom-supported MoSe2 piezoelectric catalyst, named 0.9Co / MoSe2, with a Co element mass fraction of 1.050% in the catalyst.

[0053] Comparative Example 1

[0054] By performing only step (1) of Example 1, the MoSe2 piezoelectric catalyst was obtained.

[0055] Structural characterization

[0056] The different piezoelectric catalysts prepared in Examples 1-5 and Comparative Example 1 were characterized by X-ray diffraction (XRD), such as... Figure 1 As shown.

[0057] Depend on Figure 1 As can be seen, Examples 1-5 and Comparative Example 1 are all consistent with the standard card (JCPDS No: 87-2419) of 1T phase MoSe2, and no other crystalline impurity phases were detected. Compared with 2H phase MoSe2, 1T phase MoSe2 exhibits better catalytic activity due to its superior electron transport properties. In addition, no characteristic diffraction peaks related to Co species were observed in the XRD patterns of Examples 1-5, indicating that the introduced Co exists in a highly dispersed form.

[0058] Raman characterization was performed on the different catalysts prepared in Example 2 and Comparative Example 1, such as... Figure 2 As shown.

[0059] Depend on Figure 2 It can be seen that Example 2 and Comparative Example 1 are at 235.6 cm. -1 An out-of-plane Mo-Se mode of the 2H phase was observed at (A 1g The weak peaks of J1, J2, and E. In addition, J1, J2, and E... 1g J3 and E 2g 1 The vibration modes are the main signals belonging to the 1T phase, located at 117.9 cm. -1 146.9 cm -1 193.2 cm -1 281.9 cm -1 and 333.9 cm -1 Both catalysts exhibited similar characteristic peaks, and the 1T phase signal was significantly stronger than the 2H phase signal, indicating that the 1T phase mainly exists in both catalysts. Therefore, the above results demonstrate the successful preparation of the piezoelectric catalysts of Example 2 and Comparative Example 1.

[0060] The different catalysts prepared in Example 2 and Comparative Example 1 were characterized by transmission electron microscopy (TEM), and the results are as follows: Figures 3-4 As shown.

[0061] from Figure 3 and Figure 4 It can be seen that the prepared MoSe2 and 0.15Co / MoSe2 are both composed of a large number of randomly layered ultrathin nanosheets, forming a nanoflower-like structure. This helps to increase the specific surface area of ​​the catalyst, provide more edge active sites, and thus improve the catalytic efficiency.

[0062] The catalyst prepared in Example 2 was characterized by EDS, and the results are as follows: Figure 5 As shown.

[0063] Depend on Figure 5 As can be seen, signal peaks of Co, Mo, and Se were detected in the EDX spectrum, proving the presence of Co, Mo, and Se elements and indicating that Co has been successfully loaded into MoSe2.

[0064] Performance testing

[0065] The application of a piezoelectric catalytic coupling persulfate system in the degradation of sulfamethoxazole (SMX) to simultaneously generate H2 and CO syngas includes the following steps:

[0066] (1) Place 30 mg of the catalyst prepared in Examples 1-5 and Comparative Example 1 into an airtight reactor and add 50 mL of SMX aqueous solution of different concentrations (5 mg / L, 10 mg / L or 20 mg / L);

[0067] (2) The reaction system is degassed by evacuating and introducing high-purity argon to replace the air in the system in order to create an inert atmosphere reaction environment.

[0068] (3) Argon gas is introduced into the reaction system until the pressure is 1 bar, and then 90 mg of persulfate (PDS) is added.

[0069] (4) The ultrasonic equipment was turned on to carry out the piezoelectric catalytic reaction. The reaction was carried out in a gas-closed system by an ultrasonic cleaner (120W, 40 kHz), and the reaction temperature was maintained at 25 ℃ by a low-temperature circulation device for 4 h.

[0070] During the reaction, the gas mixture was collected every 30 min, and the generated gases were detected by gas chromatography. CO was analyzed using a flame ionization detector (FID), and H2 was analyzed using a thermal conductivity detector (TCD). Before and after the reaction, 1 mL of liquid sample was taken, filtered through a 0.22 μm microporous membrane, and the change in SMX concentration was determined by high-performance liquid chromatography (HPLC).

[0071] 1. Add 50 mL of a 10 mg / L SMX solution to the reaction system. The syngas yield and SMX degradation rate of the catalysts prepared in Examples 1-5 and Comparative Example 1 are as follows: Figures 6-7 As shown.

[0072] Depend on Figure 6 It can be seen that the catalysts prepared in Examples 1-5 and Comparative Example 1 produced 189.6 μmol g of syngas after 4 h of reaction. -1 (H2: 80.8 μmol g) -1 CO: 108.8 μmol g -1 ), 465.6 μmol g -1 (H2: 367.1 μmolg) -1 CO: 98.5 μmol g -1 ), 371.2 μmol g -1 (H2: 289.9 μmol g) -1 CO: 81.3 μmol g -1 ), 338.3 μmol g -1 (H2: 278.3 μmol g) -1 CO: 60.0 μmol g -1 ), 300.6 μmol g -1 (H2: 231.2 μmol g) -1 CO: 69.4 μmol g -1 ), 164.3 μmol g -1 (H2: 127.2 μmol g) -1 CO: 37.1 μmol g -1 The 0.15Co / MoSe2 catalyst prepared in Example 2 exhibited the highest syngas generation performance, 2.8 times that of unmodified MoSe2. Furthermore, with increasing Co loading, the syngas yield showed a trend of first increasing and then decreasing. This may be because insufficient active sites result in a low Co loading, while excessively high loading can mask some active sites, leading to a decrease in catalytic performance. These results indicate that the introduction of Co single atoms can promote carrier separation, thereby improving syngas generation performance.

[0073] Depend on Figure 7 It can be seen that pure MoSe2 and Co / MoSe2 with different Co loadings both have a degradation rate of nearly 100% for SMX.

[0074] 2. Application of piezoelectric catalysis coupled with persulfate system for SMX degradation and resource-based syngas generation under different SMX solution concentrations.

[0075] The syngas yield and SMX degradation rate of the catalyst prepared in Example 2 under different concentrations of SMX solution are as follows: Figure 8 As shown.

[0076] Depend on Figure 8 It can be seen that the syngas yield increases with increasing SMX concentration. Specifically, the syngas yield is 205.0 μmol g when the SMX concentration is 5 mg / L, 10 mg / L, and 20 mg / L. -1 (H2 production was 133.5 μmol g) -1 CO production was 71.5 μmol g. -1 ), 465.6 μmol g -1 (H2 production was 367.1 μmol g) -1 CO production was 98.5 μmolg. -1 ), 773.4 μmol g -1 (H2 production was 533.0 μmol g) -1 CO production was 240.4 μmol g. -1 Syngas production reached its highest level at an SMX concentration of 20 mg / L, likely due to the increased carbon source provided in the reaction system. Degradation rates approached 100% at SMX concentrations of 5 mg / L and 10 mg / L. However, at an SMX concentration of 20 mg / L, the degradation rate decreased to 74.1%, possibly due to insufficient active species in the system and competitive consumption of free radicals by intermediate products, leading to a decline in SMX degradation.

[0077] 3. Catalyst Cyclic Stability Test

[0078] The catalyst prepared in Example 2 was subjected to a cycle stability test at an initial SMX concentration of 10 mg / L. The test method was as follows: after each reaction, the catalyst in the reaction system was collected, thoroughly washed with deionized water, dried, and then reused in the next catalytic reaction to evaluate the catalyst's recyclability. The test results are as follows: Figure 9 As shown.

[0079] Depend on Figure 9It can be seen that after four cycles of reaction, the syngas yield of the catalyst in the first reaction was 450.9 μmol g. -1 The syngas yield in the second cycle was 450.8 μmol g. -1 The syngas yield from the third reaction was 444.4 μmol g. -1 The syngas yield in the fourth cycle was 436.3 μmol g. -1 The degradation rate was relatively small; meanwhile, the SMX degradation rate remained around 100% throughout the cycle. These results indicate that the prepared Co / MoSe2 piezoelectric catalyst possesses good cycling stability and reusability, meeting the application requirements in wastewater treatment and resource conversion processes.

Claims

1. A metal single-atom modified MoSe2 piezoelectric catalyst, characterized in that, The catalyst is based on MoSe2, with Co single atoms loaded onto the MoSe2 surface through a reduction reaction.

2. The single-atom modified MoSe2 piezoelectric catalyst according to claim 1, characterized in that, The catalyst has a Co single atom loading of 0.059~1.05 wt%.

3. The MoSe2 piezoelectric catalyst modified with a single metal atom according to claim 1, characterized in that, The catalyst exhibits a nanoflower-like structure composed of ultrathin nanosheets.

4. A method for preparing a single-atom modified MoSe2 piezoelectric catalyst according to any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Preparation of MoSe2 powder; (2) MoSe2 powder is uniformly dispersed in a solvent, and cobalt salt solution is added under stirring. After stirring evenly, a reducing agent is added to carry out a reduction reaction. After the reaction is completed, the precipitate is collected, washed, and dried to obtain a Co single-atom modified MoSe2 piezoelectric catalyst.

5. The method for preparing the metal single-atom modified MoSe2 piezoelectric catalyst according to claim 4, characterized in that, In step (2), the reducing agent is NaBH4, and the molar ratio of cobalt ions in MoSe2 and cobalt salt to NaBH4 is 393:1~18:

40.

6. The method for preparing the metal single-atom modified MoSe2 piezoelectric catalyst according to claim 5, characterized in that, The reduction reaction was carried out at 20-30°C for 12-16 h.

7. The method for preparing the metal single-atom modified MoSe2 piezoelectric catalyst according to claim 4, characterized in that, In step (1), the method for preparing MoSe2 powder is as follows: NaBH4, Se powder and Na2MoO4·2H2O are added to water, mixed evenly and then subjected to hydrothermal reaction; after the reaction is completed, the mixture is cooled, the precipitate is collected, washed and dried to obtain black MoSe2 powder; wherein, the molar ratio of NaBH4, Se powder and Na2MoO4·2H2O is 3~4:1.9~2:

1.

8. The method for preparing a single-atom modified MoSe2 piezoelectric catalyst according to claim 7, characterized in that, The hydrothermal reaction temperature is 180~210℃, and the reaction time is 18~20 h.

9. The application of a single-atom modified MoSe2 piezoelectric catalyst according to any one of claims 1 to 3 in the piezoelectric catalytic coupling of persulfate degradation of organic pollutants in wastewater to simultaneously generate H2 and CO syngas.

10. In the application according to claim 9, the organic pollutant is a sulfonamide antibiotic.